Gap analysis as a basis for strategic spatial planning of green infrastructure: a case study in the Ukrainian Carpathians. Issue 1 (3rd April 2017) - Angelstam, Per; Yamelynets, Taras; Elbakidze, Marine; Prots, Bohdan; Manton, Michael
ABSTRACT: Increased demand for natural resources and economic transition threaten natural and biocultural capital and thus ecosystem services for human well-being. We applied an evidence-based approach to strategic planning of functional green infrastructure in a European biodiversity hotspot: the Ukrainian Carpathian Mountains. We (1) described how potential natural vegetation types have been transformed, (2) applied evidence-based critical thresholds for each potential natural vegetation land cover, (3) measured how much of the potential natural vegetation land covers are protected, and (4) estimated the area of cultural landscapes that emerged. While only 2% of lowland land cover types were left, 55% of mountain forests and 94% of alpine land covers remained. Many mountain forests were transformed to valuable cultural landscapes. Beech and oak forests covered 42% of the study area but at low levels of protection (<5%). The highest protection level (12–17%) was in mixed beech–fir–spruce and in spruce forests. However, taking connectivity into account, only alpine land covers formed a functional habitat network. More areas need to be protected and planned to build a functional green infrastructure. Traditional village systems with biocultural values need support. We discuss how strategic analyses can encourage collaborative spatial planning and international development cooperation.